National Airline Networks : A Graph Theoretic Analysis - Sööt, Siim (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1975)
Network properties of national domestic airline Systems are examined and linked to causal factors such as levels of economic development, population size and distribution, topographic relief, and size of country. Graph theoretic indices are utilized to measure network characteristics and become the independant variables in regression analyses. The theoretical pitfalls of this method are highlighted by utilizing a path analytic framework to identify the degree of interrelationship among the dependent variables. Still, the graph theoretic method is deemed useful as a means of topologic analysis of network structures.